Implementasi Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) di Kecamatan Ampek Angkek Kabupaten Agam - Rifdah Hanun Kamilah; Fitri Yul Dewi Marta; Kiratu Hamda Puriska Siregar; Najwaa Deka Fauziyyah; Maria Fernanda Maia; Alexandria Liana Chrisvilia Way; Nafhah Rajiha Gandhi; Luthfi Azhari (Jurnal Informasi Pengabdian Masyarakat, 2026)
This study examines the implementation of the Integrated Dynamic Archival Information System (SRIKANDI) at the Ampek Angkek District Office, Agam Regency, West Sumatra Province. SRIKANDI is an official application developed by ANRI, the Ministry of Administrative and Bureaucratic Reform, BSSN, and the Ministry of Communication and Informatics as part of the Electronic-Based Government System (SPBE). This study uses a descriptive qualitative approach through participatory observation and in-depth interviews during Internship II from January to February 2026. The results show that the implementation of SRIKANDI in Ampek Angkek District is still in a transitional phase from a manual to a digital system. Using Edwards III’s model analysis, several obstacles were found, including human resource issues such as low staff digital literacy, organizational culture such as leaders’ preference for manual systems, technical constraints such as complex outgoing letter forms, and disconnected digital workflows between institutions. Supporting factors include easier archive management, high accessibility for leaders, and standardized official document procedures. The Agam Regency Government has conducted socialization since 2023 and plans to expand implementation to the nagari level in order to create an integrated digital archival ecosystem. These findings emphasize the importance of continuous training, technical assistance, and leadership commitment in strengthening the effectiveness of digital archival transformation at the district level in an optimal and sustainable manner.